2015
DOI: 10.1039/c4ra16874g
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of tungsten–benzylidyne complexes derived from s-indacene: synthesis, characterization and DFT studies

Abstract: The photophysics of the mono- and homobimetallic complexes of tungsten benzylidyne has been examined by using absorption and emission. Theoretical calculations were carried out to gain further understanding of these novel molecular systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…With this procedure, our working group has successfully synthesized several homobimetallic complexes. 17,[26][27][28]30 The NMR spectroscopic studies of both nuclei were carried out compared to previous works found in the literature. 17,35 1 H and 13 C NMR spectra show that the ruthenocene compound derived from as-indacene, (3), is produced as a sole isomer, i.e., the anti-configuration.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…With this procedure, our working group has successfully synthesized several homobimetallic complexes. 17,[26][27][28]30 The NMR spectroscopic studies of both nuclei were carried out compared to previous works found in the literature. 17,35 1 H and 13 C NMR spectra show that the ruthenocene compound derived from as-indacene, (3), is produced as a sole isomer, i.e., the anti-configuration.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Furthermore, metallocenes derived from fused delocalized polycyclic bridging ligands are frequently precursors of stable mixed-valence complexes due to a powerful electronic interaction through the spacer ligand. [26][27][28][29] The synthetic path to achieve a whole series of homobimetallic systems derived from s-indacene 27,28,30 and as-indacene 17 has been accomplished by our group to understand the electronic properties permitting the intermetallic communication in the mixed-valence compounds. Here, we describe the catalytic activity of ruthenocene bimetallic complexes derived from s-indacene, pentalene, and as-indacene and compare with ferrocene (Fc), 2,2-bis (ethylferrocenyl)propane (catocene: Cat) and their analogous iron complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The strong electronic interactions between the metal centers in organometallic complexes make them potential model systems for organometallic polymers, which might result in a range of interesting electronic, magnetic, and optical properties, [1][2][3][4][5][6][7][8][9][10][11][12] as well as useful in homogeneous catalysis due to the presence of cooperative chemical effects. 3,[13][14][15][16][17] A suitable approach to access these type of materials is the introduction of organometallic units, such as oligomers or polymers, due to their high structural diversity and architectonic flexibility, owing to the versatility and different oxidation states of the redox centers.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 One of the requirements to achieve a conducting organometallic polymer, is that the spacer ligand bearing different redox centers must be suitable to favor the electronic communication between those redox centers. 5,[20][21][22][23][24] In this matter, fused delocalized polycyclic bridge ligands, such as pentalene and indacene, are particularly effective to promote the interaction between different redox centers due to their geometry, rigidity, and electron-rich π system. 2,5,16,21,23 The main difficulty to attain organometallic polymers, is the decrease in solubility as the number of organometallic units increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation